Tonalites from the Hospitais Massif (Ossa-Morena Zone, SW Iberian Massif, Portugal): I: Geological setting and petrography - Moita, P. (2015)
The Hospitais Massif is an elliptical-shaped plutonic body, with a WNW-ESE long axis, located in the western Ossa-Morena Zone domains in Portugal. This massif, composed essentially of tonalites, is part of an igneous association, ranging from gabbros to granites, intrusive in a gneissic-migmatitic complex, as part of the Évora High-grade Metamorphic Terrains. The tonalites present magmatic fabrics associated with a moderately developed foliation, recording syntectonic crystallization and cooling, co-planar to steep foliations observed within the surrounding sheared gneisses and migmatites. From field and petrographic studies, it is possible to suggest that the deformation of the tonalites and associated basic rocks was synchronous with Variscan progressive shearing of the gneisses and migmatites envelope.